2006
DOI: 10.1007/1-4020-4025-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations, Information, Gravity and the Quantum Potential

Abstract: We show how the quantum potential arises in various ways and trace its connection to quantum fluctuations and Fisher information along with its realization in terms of Weyl curvature. It represents a genuine quantization factor for certain classical systems as well as an expression for quantum matter in gravity theories of Weyl-Dirac type. Many of the facts and examples are extracted from the literature (with references cited) and we mainly provide connections and interpretation, with a few new observations. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
144
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(158 citation statements)
references
References 123 publications
(298 reference statements)
0
144
0
14
Order By: Relevance
“…Equation (19a) is the Wigner equation governing the Wigner distribution functions given by equation (19b) [13]. Therefore, we call the new form of the EPS obtained by transformation (13) on the old one for β = α = − 4 Quantum potential and generalization to the EPS a) Quantum potential in q space.…”
Section: The Extended Canonical Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (19a) is the Wigner equation governing the Wigner distribution functions given by equation (19b) [13]. Therefore, we call the new form of the EPS obtained by transformation (13) on the old one for β = α = − 4 Quantum potential and generalization to the EPS a) Quantum potential in q space.…”
Section: The Extended Canonical Transformationsmentioning
confidence: 99%
“…The interaction of the particle and the field is attributed to a scalar potential that turns out to be quantum potential, whenever, the constraint of the invariance of Schrödinger equation is applied. The connection of quantum potential with quantum fluctuations and quantum geometry in terms of Weyl curvature has been studied extensively by different authors; see, for example F. and A. Shojai [12], Carroll [13] and the references therein. However, unlike the external potential, the quantum potential is not a pre-assigned function of the system coordinates and can only be derived from the wave function of the system [6] or from the corresponding quantum distribution functions used to calculate the average values of the observables.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus natural that there are numerous attempts to reformulate quantum mechanics in a more geometrical way [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Using the language of [21,22], it was shown that such trajectories naturally arise in the configuration space for the complex Klein Gordon equation. It was further found that the evolution equation for those trajectories can be cast in the form of a geodesics equation in a conformally rescaled configuration space [2,3,7,9,18,19]. Thus, the relativistic Klein Gordon equation can be rewritten in a geometric language with non-trivial trajectories in configuration space.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the particle and field is attributed to a scalar potential that turns out to be the quantum potential. The connection of the quantum potential with quantum fluctuations and quantum geometry in terms of Weyl's curvature has been studied by F. Shojai and A. Shojai [7] and Carroll [8]. Nevertheless, unlike the external potential, the quantum potential is not a pre-assigned function of the system coordinates and can only be derived from the wave function of the system [5] or from the corresponding quantum distribution functions used to calculate the average values of the observables [9].…”
Section: Introductionmentioning
confidence: 99%